2012
DOI: 10.1094/pdis-06-11-0477
|View full text |Cite
|
Sign up to set email alerts
|

Spot Form of Net Blotch Resistance in a Diverse Set of Barley Lines in Australia and Canada

Abstract: McLean, M. S., Howlett, B. J., Turkington, T. K., Platz, G. J., and Hollaway, G. J. 2012. Spot form of net blotch resistance in a diverse set of barley lines in Australia and Canada. Plant Dis. 96:569-576. The responses of 95 barley lines and cultivars to spot form of net blotch (SFNB) caused by Pyrenophora teres f. maculata were analyzed as seedlings and adults in Australia and Canada. Cluster analyses revealed complex reaction responses. Only 2 lines (Esperance Orge 289 and TR3189) were resistant to all isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…The distribution of SFNB infection types across the BCC accessions analyzed indicated that susceptibility or resistance is polygenic in nature consistent with previous studies (33,44,68,69). The distribution of SFNB infection types across the BCC accessions analyzed indicated that susceptibility or resistance is polygenic in nature consistent with previous studies (33,44,68,69).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The distribution of SFNB infection types across the BCC accessions analyzed indicated that susceptibility or resistance is polygenic in nature consistent with previous studies (33,44,68,69). The distribution of SFNB infection types across the BCC accessions analyzed indicated that susceptibility or resistance is polygenic in nature consistent with previous studies (33,44,68,69).…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, NFNB resistance QTL have been identified throughout the genome (33); however, resistance to both forms of the net blotch pathogen were rarely identified in similar locations (20,39), suggesting that the majority of resistances are distinct for the different forms of P. teres and in regards to breeding, the two need to be treated as separate diseases. Growing barley cultivars with genetic resistance to SFNB and NFNB is the most sustainable strategy of disease management (33,44). However, the diversity of virulence/avirulence genes within the pathogen populations and complexity of the interaction with host susceptibility targets and resistance genes requires robust genetic characterization of both the host and pathogen to understand the underlying genetic interactions involved.…”
Section: Discussionmentioning
confidence: 99%
“…One experiment was sown using the conditions described by McLean et al (2010;2012), in which ten replicates of each treatment were sown with two seeds in 5 cm pots containing potting mixture supplemented with trace elements, nitrogen as isobutylidene diurea (IBDU), osmocote fertilizer, lime and iron. Treatments were arranged in a randomised complete block design and seedlings grown in a glasshouse, inoculated to leaf wetness with a spore and mycelium suspension (~2x10 3 parts/ml) of P. teres f. maculata isolate 03-0007 at the 2-3 leaf stage.…”
Section: Glasshouse Experimentsmentioning
confidence: 99%
“…Disease management tactics for SFNB consist of fungicide application, inoculum reducing cultural practices, and the introgression of resistance into popular cultivars (22,26). Very little research has been documented to recommend specific barley accessions as effective resistance sources for SFNB.…”
mentioning
confidence: 99%
“…Very little research has been documented to recommend specific barley accessions as effective resistance sources for SFNB. Likewise, McLean et al (22) evaluated the responses of 95 barley accessions and cultivars to SFNB seedling and adult plant resistance in Australia and Canada and found that only two were resistant to all isolates tested, whereas 15 accessions, including cultivars, were resistant to the Canadian isolates tested and a mixture of Australian isolates at the adult plant stage. Likewise, McLean et al (22) evaluated the responses of 95 barley accessions and cultivars to SFNB seedling and adult plant resistance in Australia and Canada and found that only two were resistant to all isolates tested, whereas 15 accessions, including cultivars, were resistant to the Canadian isolates tested and a mixture of Australian isolates at the adult plant stage.…”
mentioning
confidence: 99%